e-Monep Policy Implementation in Regional Development Administration of Gorontalo Regency - Kiraman, Albert Oktavian; Hamim, Udin; Nggilu, Rukiah; Lilik Istiqomah (Walidem Institute and Publishing, 2025)
Objective: This study aims to assess the effectiveness of the implementation of the e-Monep policy in the Development Administration Section of the Boalemo Regency Regional Secretariat by identifying obstacles in the organizational, interpretation, and implementation dimensions, as well as formulating improvement recommendations based on empirical findings. Theoretical framework: Using the Charles O Jones policy implementation framework that examines organization, interpretation, and implementation as an analytical basis for implementing capacity, policy interpretation processes, and operational practices. Literature review: Includes studies of public policy implementation, electronic governance for monitoring, evaluation, and reporting of local governments, and public sector change management with a focus on human resource competencies, information and communication technology infrastructure, cross-unit coordination, and policy communication. Method: The study used a descriptive qualitative approach from August to September 2025 with thirteen informants through purposive and snowball sampling; data were collected through interviews, documentation, and observation; analysis included reduction, presentation, conclusion drawn, and verification using credibility tests. Results: The organizational dimension has not been optimal due to limitations in competence, facilities, and coordination; the interpretation dimension is relatively adequate through routine socialization and effective communication; the implementation dimension has not achieved the goals due to input delays, technical constraints, and infrastructure limitations. Implications: It is necessary to strengthen operator competence, provide and maintain infrastructure, strengthen cross-unit coordination, standardize procedures, establish clear performance indicators, discipline input schedules, as well as provide technical support and data standardization. Novelty: Systematic application of the Jones framework in the context of the current e-Monep region that reveals the asymmetry of progress between dimensions and marks a lever point for improvement in competence, facilities, and coordination.